Piękno i groza współczesnego Babilonu: obraz Londynu w wybranych XX-wiecznych angielskich opowieściach kryminalnych = The beauty and the horror of modern Babylon: the image of London in selected 20th-century English detective stories - Kallas, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the present essay is to study the origins and variegated meanings of the striking metaphor LONDON IS THE MODERN BABYLON, widespread since at least the early 19th century. What did the notion of "Babylon" actually mean to the Victorians? What made London its pre-eminent modern incarnation? What aspects of the British capital made people compare it to the legendary ancient metropolis?
Keywords: powieść kryminalna; literatura angielska; 20 w.